Web-based worksheets to improve student learning outcomes: A design and implementation - Zen, Zelhendri; Ozila, Amalini Lutfia; Yeni, Fetri (Journal of Education and e-Learning Research, 2025)
The purpose of this study is to design web-based worksheets as a solution to improve learning outcomes of Indonesian history in senior high school. This study adopted Plomp's model and experimental design to analyze the improvement of learning outcomes. Nine experts and 35 eleventh-grade students (aged 16.60±0.51 years) participated voluntarily consisting of males (n1=16) and females (n2=19). The implementation of this web-based worksheet was conducted with blended learning that lasted for 6 weeks. Data were collected through questions in the worksheet and then analyzed by descriptive, percentage, and t-tests. The findings showed that the experts' assessment of the web-based worksheet obtained an average of 88.41. The implementation showed that students' learning outcomes improved after using the worksheet (n=35; t=27.664; MD=31.46; sig.<0.05; pre-test 57.71±6.90 and post-test 89.17±4.57). There was no significant difference in learning outcomes between male and female students (t=1.824; MD=2.734; sig.>0.05; post-test 87.69±4.83 and 90.42±4.05). This worksheet can be used to overcome the limitations in learning Indonesian history, which has a positive impact on students' learning outcomes. A wider participant base with more complex learning materials, design, and appearance is needed for future research.